Measuring and managing liquidity risk - Castagna, Antonio; Fede, Francesco (Chichester, West Sussex, U.K. : Wiley, 2013)
This is a fully up-to-date, cutting edge guide to the measurement and management of liquidity risk. Written for front and middle office risk management and quantitative practitioners, it provides the ground-level knowledge, tools and techniques for effective liquidity risk management. Written with a highly practical cut, though thoroughly grounded in theory, the book begins with the basics of liquidity risks and, using examples pulled from the recent financial crisis, how they manifest themselves in financial institutions. The book then goes on to look at tools which can be used to measure l.
7.6 The term structure of available funding and the liquidity buffer7.6.1 The term structure of forward cumulated funding and how to use it; 7.7 Non-maturing liabilities; 7.7.1 Pricing of NML and cost of the liquidity buffer; 7.8 The second cause of the liquidity buffer: Collateral margining; 7.8.1 A method to set the liquidity buffer for derivative collateral; 7.8.2 The cost of the liquidity buffer for derivative collateral; 7.9 The third cause of the liquidity buffer: Off-balance-sheet commitments; 7.10 Basel III regulation and liquidity buffer; 8 Models for market risk factors.
8.1 Introduction.
Includes bibliographical references and index.
Online resource; title from PDF title page (Wiley, viewed September 12, 2013).
Keywords: Liquidity (Economics); Financial risk; BUSINESS & ECONOMICS -- Finance; Financial risk; Liquidity (Economics); Electronic books; Electronic books